When will service standards in Singapore improve? - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2009)
Are service standards in Singapore bad, or do Singaporeans expect too much from service providers? Ask any Singaporean about their service experiences and you might evoke strong reactions, accompanied by vivid stories spun out of petty encounters with service providers. Ask a local service provider, however, and you might hear tales of rude, thankless customers. Those in the business of providing service often find themselves walking a thin, fine line between protecting the interests of customers and front-line service personnel. If businesses subscribe to the adage, “the customer is always right”, is it fair to expect those in the “wrong” to provide great service?